Independent study and technology education: Procedures for the professional education of teacher trainees - Fontes Guerrero, Olga Lidia; Martínez Torres, Milton J.; Mirabal Cruz , Henry Yasmel (Transformación, 2024)
Objective: This article aims to illustrate the activities to be used to develop independent study through the use of technology, based on the professional training of the future teacher.Method: The authors rely on theoretical methods and the systemization of experiences to collect the data herein presented.Results: The main finding is a set of procedures for professional education of teacher trainees The proposed activities are a constituent part of the main result of this inquiry.Conclusion: The proposed activities allow the student to work independently with new technologies (mobile phones, tablets, laptops) outside the classroom while reaching a higher level of communicative competence since it favors the production of a varied and creative language through the application of interactive programs, which will favor the improvement of instruction and education processes.
Keywords: teacher education; educational technology; independent study; professional training